Perancangan Sistem Pengendali Jarak Jauh Berbasis Mikrokontroler Pada Rumah Cerdas - Lewi Lewi; Abdul Rahman (Jurnal Teknik Mesin Sinergi, 2020)
In the construction of a house, the model or design is often the main priority, while the electrical installation is not given much attention. As a result, the need for electrical energy is increasing rapidly. In addition, the increasing demand for electrical energy is also due to a lack of supervision and control over household electricity consumption. A simple solution to save energy while facilitating monitoring of electrical energy use is a system that integrated with various devices in the house. This system is also necessary because it can be controlled by the owner of the house remotely, namely by short message (SMS). This control system is controlled by an Arduino microcontroller as a control center connected to a device to turn on the lights. The microcontroller is connected to the GSM Shield which functions as a device that receives messages as short as those sent by the home owner. The contents of the message received by the GSM Shield will be read by the microcontroller and if the contents of the message are correct, the microcontroller can give instructions to the device to turn on the light.